Critical Discussion Analysis of Online News Media Text in Implementation of PSBB during Pandemic Covid-19 - Pratiwi, Retna Isti; Setiawan, Teguh (Budapest International Research and Critics University, 2021)
Online media plays an important role in reporting during the pandemic. Various case issues and changes in people's behavior are easily accessible through online news. This study aims to explain how the structure of the text which includes the macro structure, micro structure and superstructure is displayed in the news text about the implementation of PSBB at the closing ceremony of McDonald's, cognitive analysis and social analysis that influence journalists as news writers in revealing PSBB violations. The research method used is a qualitative method with the technique of critical discourse analysis of the Teun A. Van Dijk model which includes 3 dimensions, namely the dimensions of text, social cognition and social context. The data is in the form of online news published in three media, namely kompas.com, tempo.com and detik.com which aired in May 2020 with the news theme